IRASIONALITAS PERSYARATAN PENCALONAN PERSEORANGAN DALAM UNDANG-UNDANG PEMILIHAN KEPALA DAERAH - Maskup Asyadi (Universitas Kristen Satya Wacana, 2021)
This writing attempts to discuss the irrationality of independent nomination requirements in the regional head elections proceedings which hereinafter shall be referred to as the election. The irrationality of this independent nomination requirements ultimately pushes the smaller chance of an independent candidate to compete in the election. One form of this irrationality can be seen from the high standard endorsement requirements for the independent candidate. In addition to that, the irrationality is made even worse by the registration mechanism through the Silon Application owned by the General Elections Commission/ Komisi Pemilihan Umum (KPU) which implementation is more complicated for independent candidate pairs compared to candidate pairs that are endorsed by a political party. The present of a pair of independent candidates however can be a balance for the parties where the candidacy process so far has been conducted in a dark room. Whereas with the increased level of difficulty for the pair of independent candidates to compete in the election, it also means that is will be difficult to attain the mandate and philosophy of Article 28H paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Furthermore, on the other hand, due to the difficulties for independent candidates, it promotes the increase growth of recent elections with only single candidates. This matter is detrimental for the community who are the voters and holders of sovereignty.